Socialization of Gastritis and Gastroenteritis Prevention through the Introduction of Helicobacter pylori and Escherichia coli to the Community - Rahmawati; Yudisthira Yudisthira; Arif Sujatmiko; Sofiani Sari; Siti Hardianti; Desy Lustiyani Rajagukguk (JURNAL PENGMAS KESTRA (JPK), 2026)
Gastritis and gastroenteritis are gastrointestinal infectious diseases that remain significant public health concerns, particularly in areas where Clean and Healthy Living Behavior (PHBS), personal hygiene, and environmental sanitation have not been optimally implemented. Gastritis is commonly associated with Helicobacter pylori infection, whereas gastroenteritis is often caused by pathogenic bacteria, including Escherichia coli. Limited public knowledge regarding the causes, modes of transmission, risk factors, and preventive measures for these diseases may increase the risk of infection. Therefore, this Community Service Program aimed to improve public knowledge and awareness of gastritis and gastroenteritis prevention through the introduction of Helicobacter pylori and Escherichia coli. The activity involved 30 participants and was conducted through health education sessions, interactive discussions, question-and-answer sessions, and the use of educational media, including posters and leaflets. The effectiveness of the program was evaluated using pre-test and post-test assessments to measure participants' knowledge before and after the educational intervention. The results showed that the mean knowledge score increased from 61.3 (moderate category) in the pre-test to 91.7 (very good category) in the post-test. These findings indicate that the educational intervention was effective in improving participants' understanding of the causes, transmission routes, symptoms, risk factors, and preventive measures for gastritis and gastroenteritis through the implementation of Clean and Healthy Living Behavior (PHBS), proper hygiene, environmental sanitation, and food safety practices. This community service activity is expected to enhance public health literacy and encourage sustainable healthy behaviors to prevent gastrointestinal infectious diseases.